2011
DOI: 10.1159/000335355
|View full text |Cite
|
Sign up to set email alerts
|

Association between Nerve Growth Factor Gene Polymorphism and Executive Dysfunction in Japanese Patients with Early-Stage Alzheimer’s Disease and Amnestic Mild Cognitive Impairment

Abstract: Background/Aims: To address the clinical neurocognitive roles of nerve growth factor (NGF) genetic polymorphism in early-stage Alzheimer’s disease (AD) and amnestic mild cognitive impairment (A-MCI), we investigated the association between this single-nucleotide polymorphism (SNP) and executive dysfunction as a nonmemory cognitive impairment. Methods: Among 200 outpatients with dementia and MCI whose NGF SNP rs6330 genotype was identified, those with A-MCI (n = 35) and early-stage AD (n = 67) were recruited an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 98 publications
(90 reference statements)
1
10
0
Order By: Relevance
“…Our results may help to elucidate the functional roles of not only the NT-3 gene, but also other neurotrophin gene polymorphisms described in previous studies [17,18,23,24]. Furthermore, elucidating the detailed associations between NT-3 gene diversity and behaviors in patients with AD will be an important task in the future.…”
Section: Nt-3 Polymorphisms In Adsupporting
confidence: 51%
See 2 more Smart Citations
“…Our results may help to elucidate the functional roles of not only the NT-3 gene, but also other neurotrophin gene polymorphisms described in previous studies [17,18,23,24]. Furthermore, elucidating the detailed associations between NT-3 gene diversity and behaviors in patients with AD will be an important task in the future.…”
Section: Nt-3 Polymorphisms In Adsupporting
confidence: 51%
“…Moreover, NT-3 protects cortical neurons against A-β dependent neural cell death by limiting caspase-8, caspase-9 and caspase-3 cleavage [16]. While some previous studies have reported neurotrophin polymorphisms as a risk factor for AD in Japanese populations, our group reported that representative single-nucleotide polymorphisms (SNPs) of NGF and BDNF influenced executive function during limited demented stages, as assessed using the frontal assessment battery (FAB) [17][18][19][20][21].…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…A recent study showed that Val66Met determines the differences in the age-related effects on hippocampal volume and cognitive function between valine homozygosity (Val/Val) and methionine (Met) carriers [16][17][18]. Moreover, we found that a nerve growth factor polymorphism (rs6330) influences the executive function of mild-stage AD and A-MCI patients in a recent study [19]. These results imply that the effects of neurotrophin gene polymorphisms on cognitive function may be altered during the aging process or according to the stage of neurodegeneration.…”
Section: Introductionmentioning
confidence: 56%
“…It has been widely applied in studies on various target groups [17,18,19,20,21]. Researchers have discovered that neural substrates related to performances on the FAB include both cortical and subcortical areas, such as the middle frontal gyrus, inferior frontal, insula [22], callosomarginal, and precentral regions [23].…”
Section: Introductionmentioning
confidence: 99%